MATHETICAL STEPS IN PRODUCING LOWLAND RICE BY APPLICATIONS OF FURROW IRRIGATION AND FERTILIZERS - Alhaji Batagi, Shehu; Danladi, Hakimi; Adamu, Lawal; Daniya, Emmanuel (FUDMA Journal of Sciences, 2026)
AbstractFluctuationin weather, insufficient macro and micro nutrients in the soil are hindering lowland rice production and also other crops production leading to shortages of food in Nigeria and the world at large.In this research work, the combination of four fertilizers NPK (W), Nitrogen (N), Zinc (Z), Selenium ( ) fertilizers and furrow irrigation ( ) were applied as variables as mathematical steps and tested in the farm field of National Cereal Research Institute Baddegi, Niger State, Nigeria. The values of the variables above were collected from the same Institute and analysed by   software. The adequate performance of N, W, Z,  and   demonstrated large yields of lowland rice production with optimum production of 6 to 7 bags of lowland rice per hectare. Moreover, it was observed that the combination ofN, W, Z,  alongside with    had potential influence on the large yields of lowland rice production.
Keywords: Fertilizers; Furrow Irrigation; Lowland; Mathematical model; Rice